Benchmarking Performance of a Gate-All-Around Germanium Nanotube Field Effect Transistor (GAA-GeNTFET) against GAA-CNTFET. (15th February 2017) - Bayani, Amir Hossein; Dideban, Daryoosh; Akbarzadeh, Mojtaba; Moezi, Negin
Abstract : Two gate-all-around field effect transistors (GAA-FETs) based on carbon and germanium nanotubes are proposed. The electronic properties and analog performance of the FETs are theoretically calculated and compared with each other. Also, by adding 5 × 10 19 dopant/cm 2 doping concentration in the source and drain regions, the results are re-obtained. Non-equilibrium Green's function method within the tight-binding Hamiltonian, which is extracted from density functional theory through the Wannier function, are used to calculate the output results. From the transfer characteristics analysis for nanotubes with the same chirality, it can be found that the ON- and OFF-currents for GeNTFET is about ten times smaller than that of CNTFET. Moreover, by adding dopants in the source and drain regions, the ION increases for both devices. The ION /IOFF ratio for all proposed FETs is almost the same and it is of order 10 4 . We also found that the subthreshold swing for doped CNTFET is smaller than the other examined devices. The output characteristic of the CNTFET shown a saturation current when the drain voltage reached to 0.4 V, while this value for GeNTFET is equal to 0.6 V. Comparison between CNTFET and GeNTFET with the same chirality shows that the CNTFET has a better transistor performance but when comparing is performed on the same diameter of CNT and GeNT FETs, results show better transistor performance of GeNTFET compared to the CNTFET.